Mute articulations representing the body when the self isn't what it used to be - Verwey, Adala Michelle Prévost (Centre for Film and Media Studies, 2014)
The topic of my research is an exploration of the concept of the 'mute body. The mute body is the body which stages a certain inderminacy and distance from the viewer. It is a form of hiding, but also a form of play with narcissistic implications and perhaps even seductive intent. The mute body is a response to the fear of power and what power has done to bodies in history. Conversely, it is also the location of power - the exercising of the choice to remain silent is a wilful act of retention or withholding. The mute body is not the vacant body. It is the body of which we are unable to say with certainty whether it is unable to signify or unwilling to signify.